Sosialisasi Pencegahan Stunting Melalui Program DAHSYAT dan Peningkatan Kesadaran Masyarakat Tentang Pemenuhan Gizi di Desa Losari, Kecamatan Grabag, Kabupaten Magelang - Tiyas, Fitri Ariyaning; Sarwadhamana, Raden Jaka (Bangun Desa: Jurnal Pengabdian Masyarakat, 2023)
Stunting is a growth delay characterized by chronic malnutrition due to inadequate intake during the first 1,000 days of life, resulting in growth retardation in children under five. The prevalence of stunting under five in Indonesia is 24.4% in 2021. The target for reducing stunting in Indonesia has been set at 14% in 2024. This shows that Indonesia is experiencing serious public health problems in cases of stunting under five. One of the efforts to overcome stunting in toddlers is socialization and education to the community in order to increase knowledge and awareness of stunting prevention, as well as education in providing supplementary food by utilizing locally sourced food ingredients as well as increasing knowledge and training of Posyandu cadres. The method used in this study uses the question and answer lecture method between the participants and the material. The success of this socialization activity can be seen from the enthusiasm of the community and cadres who also attended the socialization event. The community in Losari Village also actively participates in the activities provided where participants provide feedback (discussion and question and answer) related to the material that has been delivered..Keyword: prevention, stunting, dahsyat